Art of Music Taring In Sanggar Tunas Muda Lahat District In Perspective Aksiologi: Study In The Context Of Socio Culture - Arief, Ahmad Fikri; Sunarto, Sunarto; Triyanto, Triyanto (Universitas Negeri Semarang, 2017)
The art of Terbangan music in Lahat district is a cultural product derived from the customs of Semende people who migrated to the district of Lahat South Sumatra. With regard to this, the purpose of this study is to examine the issue of the form of the music of Terbangan and the axiological values ​​in it. This research uses an interdisciplinary approach involving the disciplines of musicology and philosophy. Science of Musicology is used to analyze the elements and forms of music on the art of flying. The discipline of philosophy is used to analyze the values ​​contained in the Art of Music Terbangan. Sources of data in this study using a qualitative source consisting of primary and secondary sources with techniques perngumpulan observation data, interviews and document studies. Data validation technique used by source triangulation while data analysis technique is done by reducing data, presenting data, and verifying data. In this verification process, conclusions are drawn with interpretations that use emic point references (field opinion sources) and ethical perspectives based on the theoretical concepts used. Based on the results of research shows things as follows the first form of musical structure among other elements, motives, clauses, sentences or periods that exist in the art of music Terbangan. The two human values ​​in the art of Terbangan which are part of man are holiness, goodness, truth and beauty.